FRI0159 Long-term effectiveness and safety of adalimumab in patients with moderate versus severe rheumatoid arthritis. (23rd January 2014) - Burmester, G.; Matucci-Cerinic, M.; Navarro-Blasco, F.; Oezer, U.; Kary, S.; Unnebrink, K.; Kupper, H.
Abstract : Background: Evidence suggests that patients (pts) with moderate rheumatoid arthritis (RA) despite DMARDs gain benefit from anti-TNF therapy; however, to be eligible for reimbursement, pts often require severe disease activity to initiate anti-TNFs. Objectives: To compare treatment responses and adverse events (AEs) between pts with moderate versus severe RA. Methods: ReAct enrolled pts with active RA (DAS28[ESR]>3.2) despite DMARD treatment for open-label adalimumab (ADA) therapy for 12 wks or until country approval for ADA; pts were eligible to enroll in ReAlise within 12 months upon completion of ReAct. This post hoc analysis stratified pts by baseline (BL) disease activity, defining moderate disease activity as DAS28 >3.2 to <5.1, and severe disease activity as DAS28≥5.1. Analyses on data as observed (without imputation of missing data) were used to calculate treatment responses (ACR criteria), the percentage of pts with DAS28 and SDAI low disease activity (LDA) and remission, and functional ability (Disability Index of the HAQ, HAQ-DI) at intervals after the 1st dose of ADA during ReAct. Results: Of 6610 pts enrolled in ReAct, 3435 (52%) elected to continue in ReAlise; of these, 1805 (53%) completed the study. At BL of ReAct, 1267 (19%) had moderate and 5343 (81%) had severe disease activity. Pts with severe disease activity had slightly increased mean age and disease duration; as expected, these pts had higher mean values for indicators of disease activity (eg, swollen/tender joint counts, ESR/CRP levels, and HAQ-DI). In both groups, initial responses to treatment were maintained through 5 years of ADA treatment. After 5 years of ADA, ACR20/50/70 responses were greater among pts with severe disease activity, while more pts with moderate disease achieved states of LDA and remission (table ). Correspondingly, absolute values of DAS28 and HAQ-DI were lower among pts with moderate disease, yet the mean percent change in DAS28 and HAQ-DI were comparable, if not greater, among those with severe disease (table ). Incidence of AEs was comparable between pts with moderate and severe disease, eg, AE leading to discontinuation (8.2 vs. 8.7 E/100PY), serious AEs (13.3 vs 15.3 E/100PY), serious infections (3.2 vs. 3.0 E/100PY). Conclusions: Through 5 yrs of ADA treatment, more pts with moderate disease activity were able to achieve treatment targets of LDA and remission. By comparison, pts with severe disease had greater clinical response rates and a similar degree of improvement, while fewer of these pts achieved LDA and remission. Given the impact of achieving these targets on preventing structural damage and preserving function, these findings support the use of anti-TNF in RA pts with moderate disease. There were no noticeable differences in the safety profile for ADA between pts with moderate and severe BL disease activity. Disclosure of Interest: G. Burmester Grant/Research support from: Abbott, Essex/Schering-Plough, Novartis, Roche, Wyeth, Consultant for: Abbott, Essex/Schering-Plough, Novartis, Roche, M. Matucci-Cerinic: None Declared, F. Navarro-Blasco Grant/Research support from: Roche, U. Oezer Employee of: Abbott, S. Kary Employee of: Abbott, K. Unnebrink Employee of: Abbott, H. Kupper Shareholder of: Abbott, Employee of: Abbott